Molecular detection of Enterocytozoon bieneusi in alpacas (Vicugna pacos) in Xinjiang, China - Zhang Qiyuan; Wang Haiyan; Zhao Aiyun; Zhao Wei; Wei Zilin; Li Zhiguo; Qi Meng (Parasite, 2019)
Enterocytozoon bieneusi, an obligate intracellular pathogen, can infect a wide variety of hosts. This study aimed to determine the prevalence and molecular characteristics of E. bieneusi in alpacas (Vicugna pacos) in China. A total of 185 alpaca fecal samples were collected from five herds in Tacheng, Wensu, Hejing, Qinghe, and Nilka counties in Xinjiang Uygur Autonomous Region. Enterocytozoon bieneusi was detected by nested PCR of the internal transcribed spacer (ITS) region. Twenty-eight fecal samples (15.1%, 28/185) were positive for E. bieneusi, with the highest prevalence in alpacas from Qinghe (42.9%, 15/35). Four E. bieneusi genotypes were identified, which included two known (P and ALP3) and two novel (ALP7 and ALP8) genotypes. Genotype ALP3 was the dominant genotype (57.1%, 16/28), followed by genotypes P (32.1%, 9/28), ALP7 (7.1%, 2/28), and ALP8 (2.6%, 1/28). Phylogenetic analysis revealed that three genotypes (P, ALP7, and ALP3) clustered into group 1, whereas genotype ALP8 clustered into group 8. This is the first report of E. bieneusi infection and genetic diversity in alpacas from Xinjiang, China.